Bellini duct carcinoma - Gil Falcão; Anuraj Quiran Parmanande; Catarina Araújo; João Vasco Barreira (University of São Paulo, 2021)
The modern era has brought an appreciation that renal cell carcinoma (RCC) includes diverse subtypes derived from the various parts of the nephron, each with its distinctive genetic basis and tumor biology. Carcinoma of the collecting ducts of Bellini (CDC) is a rare subtype of RCC, with a predictably poor prognosis. This rare subtype represents less than 1% of all kidney carcinomas. It derives from presumably numerous chromosomal losses. It is of chief importance to differentiate CDC from other types of renal cell cancer. Typically, it is characterized by a firm, centrally located tumor with infiltrative borders. Regarding the histopathologic characteristics, we can find complex, highly infiltrative cords with inflamed (desmoplastic) stroma, with high-grade nuclei and mitoses. Most reported cases of CDC had been high grade, advanced stage, and unresponsive to conventional therapies. This rare form of disease highlights the importance of multidisciplinary teams in the management of cancer patients.